Ectomesenchymal Chondromyxoid Tumour of the Dorsal Tongue Presenting with Impaired Speech - Laura A. Schep; Martin J. Bullock; S. Mark Taylor (Case Reports in Otolaryngology)
Ectomesenchymal chondromyxoid tumours (ECTs) are rare mesenchymal soft tissue neoplasms that typically present as a slow-growing asymptomatic mass on the anterior dorsum of the tongue. Our patient presented with impaired speech articulation and pain associated with upper respiratory tract infections when the lesion on his dorsal tongue would swell, and he would accidentally bite down on it. Microscopically, ECTs appear as unencapsulated, well-circumscribed proliferations of uniform round to fusiform cells embedded within chondromyxoid matrices. Most cases of ECT have been detected in the third to the sixth decades of life, with no sex preference. ECT may cause a range of symptoms that negatively impact patients’ quality of life, including pain, dysphagia, odynophagia, bleeding, and, in the case of our patient, impairment of speech. We provide a unique preoperative clinical photograph and case description that should help readers in recognizing this neoplasm. Considering the rarity of ECT presenting clinically as well as in the literature, we believe this report will add to our growing understanding of ECT and its management. We report a case of ECT presenting on the anterior dorsal tongue that was successfully surgically resected under local anesthesia with clear margins, accompanied by a review of the pertinent literature.